The design of modified atmosphere perforated plastic packaging for fresh chillies : a thesis presented in partial fulfilment of the requirements for the degree of Master of Technology in Packaging Technology at Massey University - Weerawate, Utto (Massey University, 2001)
The quality of fresh chillies changes rapidly and under the Thai ambient conditions (30 ± 5 °C and 75 ± 5 % RH), these products spoil in a short time frame. This rapid quality deterioration causes a direct loss in returns to growers and marketers. The objectives of this study were to design a modified atmosphere perforated plastic packaging system to extend shelf life and marketability of fresh chillies. Physiological data about fresh green 'Cayenne' chillies was measured; respiration rate, internal partial pressure of O (P O ) and CO (p CO ), skin permeance to O (P′O ), CO (P′CO ) and water vapour (P′HO) as well as, water activity (a ). The extent to which these attributes were affected by a range of temperatures 5, 10, 20 and 30°C was also characterised. Respiration dramatically increased as storage temperature was increased from 5 to 30°C, whilst P′O and P′CO slightly increased. The differing effects of temperature on these two variables were responsible for the depression of internal partial pressure of O and elevation of CO internal partial pressure. The skin permeances to O and CO were very close (approximate ratio P′CO :P′O as 1.06) and it was determined that the major pathway for gas exchange of green 'Cayenne' chillies was dominated by movement through pores (through the stem area), rather than the cuticle. Average value of skin permeance to water vapour of green 'Cayenne' chillies was 201.78 nmol·s ·m ·Pa . Water vapour permeances were inconsistent over the 5-30°C temperature range due to errors from thermistor probes and environment around chillies. Surface area of green 'Cayenne' chillies provided the positive relationship with fresh weight, volume and the rate of water loss (measured at ambient temperature ≈20°C). Fresh weight and a of fresh chillies decreased as the storage temperature increased from 5 to 30°C. Storage temperatures (5, 10, 20 and 30°C) and packaging types (perforated/nonperforated plastic bags and unpackaging) had significant impact on storage qualities (colour, firmness, weight and decay) of fresh green 'Cayenne' chillies during a 2-week storage trial period. Refrigerated storage temperatures and perforated plastic bag showed promise in reducing quality attributes changes and eliminating condensation. At 5 and 10°C, no signs of chilling injury were detected on green 'Cayenne' in any packaging type used during the trial period. The atmospheres inside perforated plastic bag were similar to ambient air condition, thus ensuring that there were aerobic conditions inside. The rate of weight loss of packaged chillies varied with storage temperature, perforation area and size of perforation. The optimum storage condition and package for a 100g retail pack of chillies during a 2-week storage period is 5°C and 152.40 × 228.60 mm plastic bag with 0.49% perforation area (2.5 mm perforation size). Chillies stored under this condition had low percentage of weight loss (less than 2.5%) with no signs of chilling injury and their quality attributes were within the marketable levels. Bell peppers (Capsicum annuum L.) were used to study effects of postharvest disinfecting treatments (sodium hypochlorite (NaClO, 2%w/v) and hot water dip (HWD, 53°C 4 minutes)) on storage quality. Both disinfectants significantly reduced decay appearances on bell peppers particularly on those stored at high temperature (20 and 30°C), during a trial 2-week storage period. The application of these disinfecting treatments will be further researched on fresh chillies, for minimising decay appearance. The 'Weight Loss Simulator' model developed by Tanner (1998) was tested by comparing predicted weight loss with experimental data. The model had general agreement with the experimentally observed trends. Lack of fit of model predictions to experimental data however, was obvious in some cases. Variations, e.g. storage temperature/relative humidity, packaging and dynamic changes in biological properties of stored chillies can deviate the predicting result of this model. Sensitivity analyses performed on the model showed that the observed lack of fit could largely be explained by estimated uncertainties in the respiration rate data. From this model testing, the accuracy of the 'Weight Loss Simulator' model appeared to be limited by assumptions, input data and uncertainties occurred during data collection rather than by shortcomings in the model itself.
Keywords: Hot peppers; Packaging; Chillies